The anatomy of the seed-coat includes diagnostic characters in the subtribe Eugeniinae (Myrteae, Myrtaceae) - Sbais, Patricia Gonçalves; Machado, Nayara Carreira; Valdemarin, Karinne Sampaio; Thadeo, Marcela; Mazine, Fiorella Fernanda; Mourão, Káthia Socorro Mathias (Frontiers in Plant Science, 2022)
The subtribe Eugeniinae comprises two genera, Eugenia (ca. 1100 species) and Myrcianthes (ca. 40 species). Eugenia is the largest genus of neotropical Myrtaceae and its latest classification proposes eleven sections. This study describes the seed anatomy of forty-one species of Eugeniinae in order to provide possible diagnostic characteristics. Following standard anatomical techniques, flower buds, flowers, and fruits were processed and analyzed using microtome sections and light microscopy. The phylogeny used the regions ITS, rpl16, psbA-trnH, trnL-rpl32 and trnQ-rps16, following recent studies in the group. Ancestral character reconstruction uncovered that: the ancestral ovule in Eugeniinae was campylotropous (98.9% probability), bitegmic (98.5% probability) and unitegmic ovules arose on more than one lineage independently within Eugenia; the pachychalazal seed-coat appeared with a 92% probability of being the ancestral type; non-lignified seed-coat (24,5% probability) and aerenchymatous mesotesta (45.8% probability) in Myrcianthes pungens and in the species of E. sect. Pseudeugenia, E. sect. Hexachlamys, E. sect. Eugenia, E. sect. Pilothecium, E. sect. Phyllocalyx, and E. sect. Schizocalomyrtus, which are basal clades in the phylogeny of Eugenia are diagnostic characters for these sections; as well as the partial sclerification (only in the exotesta – exotestal seed-coat) is observed in species E. sect. Schizocalomyrtus, E. sect. Excelsae, E. sect. Jossinia (group X), and E. sect. Racemosae (22.2% probability); the exomesotestal or testal seeds in species of E. sect. Umbellatae and E. sect. Jossinia (group Y), which are two of the most recent lineages of Eugenia showed a probability of 27.2% to be the ancestral seed-coat in Eugeniinae. A dehiscent fruit is considered a plesiomorphic state in Myrtaceae; the ancestor of this family had seeds with a completely sclerified testa, and the other testa types described for the current species with dehiscent and indehiscent fruits are simplified versions of this ancestral type. Perhaps this means that the sclerified layers in the seed coat have remained in whole or in part as a plesiomorphic condition for taxa with a capsule and bacca. Maintaining the plesiomorphic condition may have represented a selective advantage at some point in the evolutionary history of the family and its groups.